Problematika Pembelajaran Bahasa Arab Nonlinguistik Pada Siswa Kelas 7 MTsN 1 Sidoarjo - DESI YATI WULAN CAHYANI; AINUN SYARIFAH (Program Studi Pendidikan Bahasa Arab Universitas Nahdlatul Ulama Purwokerto, 2024)
Learning Arabic as a foreign language raises a variety of problems, including linguistic and non-linguistic problems. This article aims to present the results of research on problems in Arabic language learning in MTsN 1 Sidoarjo, especially in grade 7F, and to find out what solutions are taken by teachers to overcome these problems. This type of research uses a qualitative approach, which means that the data collected is not in the form of numbers, but rather data from interviews, field notes, and other official documents. Meanwhile, the subject of this study is a 7F MTsN 1 Sidoarjo student as an educator who aims to obtain data on the occurrence of the Arabic language learning process. The results of the study show that non-linguistic problems are influenced by several factors, namely socio-cultural factors, teaching methods, facilities and facilities, students, environment, motivation and interests and there are several solutions to overcome these problems, namely improving supporting facilities, creating a conducive and fun classroom atmosphere, utilizing technology, revising the Arabic curriculum, improving teachers' skills, holding seminars for parents, improving variety of teaching methods and time efficiency.